The Effect of Using Youtube as a Media in English Language Learning Vocational School - Maharani, Jiharan Dwi; Kusriandi, Wendi; Suminar, Ratna Prasasti (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study describes the impact of utilizing YouTube as a medium in the context of English learning. The goal of this study is to determine whether using YouTube as a media makes learning more effective and increases students' knowledge in their English learning process. The research findings reveal that using YouTube as a medium for learning articles has a significant impact on pupils. The students subsequently completed a questionnaire and stated that utilizing YouTube as a medium improved learning effectiveness and raised their grasp of English learning.